Hodgkin’s lymphoma in a patient on adalimumab treatment for psoriasis - Alballa, Nouf; Alyousef, Alanoud; Alamari, Albatool; Alhumidi, Ahmed Abdullah; Zayed, Mohammed Ayesh; Zeitouni, Leena; Alsaif, Fahad Mohammed (AME Case Reports, 2018)
Adalimumab is a human monoclonal antibody which targets tumor necrosis factor (TNF)-alpha. It is produced by recombinant DNA technology, using a mammalian cell expression system and is widely-known to treat a number of immune-mediated conditions, including psoriasis. There has been a growing concern regarding the possible association between TNF-alpha inhibitors and malignancy. In this case report, we describe the case of a 20-year-old woman, known to have been suffering from chronic plaque psoriasis for 12 years, and who developed Hodgkin’s lymphoma within five weeks of beginning adalimumab treatment.